Knowledge, attitude and practices pertaining to healthy lifestyle in prevention and control of chronic diseases: a rapid review - Naaz, Saba (International Journal Of Community Medicine And Public Health, 2021)
With the emergence of non-communicable diseases (NCDs), healthy lifestyle has become critical to not only reduce the burden of NCDs, but also to prevent complications and severity of these diseases. Knowledge, attitude and practices (KAP) pertaining to healthy lifestyle play an important role in determining the occurrence and progress of NCDs. KAP elements are interrelated and dependent on each other. While awareness campaigns provide necessary information to people on healthy lifestyle, how well this information is utilised is a grey area. The objective of this rapid review is to understand the relationship between KAP elements pertaining to healthy lifestyle among individuals who are at risk of developing NCDs and those who are living with NCDs. For this purpose, a rapid review of articles available on Google scholar and Pubmed was conducted. Articles focusing on KAP elements pertaining to healthy lifestyle from the year 2015-2021 were reviewed. Findings from the reviewed studies suggested that people have knowledge about the harmful effects of unhealthy diet, physical inactivity, tobacco and alcohol. People have a positive attitude towards healthy lifestyle, however, being knowledgeable and having a positive attitude did not translate into practicing healthy lifestyle due to multiple barriers to translate existing knowledge into practice. Since practice scores are poor among people, existing behaviour change strategies must be re-examined. An epistemological analysis of existing human behaviour with identified barriers and facilitators to adopt healthy lifestyle can help in formulating sustainable and effective social and behaviour change interventions.